Theory of molecular fluids. Volume 2, Applications - Gray, C. G.; Gubbins, Keith E.; Joslin, C. G. (Christopher G.) (Oxford ; New York : Oxford University Press, 2011)
Existing texts on liquid theory are limited to simple liquids of spherical molecules, but nearly all liquids of practical interest have molecules that are non-spherical, resulting in more diverse phenomena. This text provides the molecular theory for such liquids, and describes applications to a wide range of physical properties.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Molecular theory; Fluids; SCIENCE / Chemistry / Physical & Theoretical; Electronic books